(untitled) (КЫРГЫЗ РЕСПУБЛИКАСЫНЫН УЛУТТУК ИЛИМДЕР АКАДЕМИЯСЫНЫН КАБАРЛАРЫ, 2022)
The article deals with rock massifs of structurally heterogeneous ore deposits in Kyrgyzstan. The data of long-term full-scale experimental studies of the stress-strain state of rock masses are summarized and the results of diagnostics of local zones of natural stress concentrations are presented.